The Influence of Family Sports Attitude on Children’s Sports Participation, Screen Time, and Body Mass Index - Lian, Yin; Peijie, Chen; Kun, Wang; Tingran, Zhang; Hengxu, Liu; Jinxin, Yang; Wenyun, Lu; Jiong, Luo (Frontiers in Psychology, 2021)
In this study, 589 children and their families were investigated to explore the relationship between parents' education level, family sports attitude, children's sports participation, screen time and children's body mass index (BMI). The results showed that: 1) There are significant differences in children's family sports attitude, sports participation, screen time and BMI with different family structure and parents' education level. 2) Family sports attitude is significantly positively correlated with parents' education level and children's sports participation, and negatively correlated with children's screen time and body mass index. 3) Children's sports participation and screen time play a chain mediating role between family sports attitude and children's body mass index, and the role is a complete mediating role. Therefore, family sports attitude can affect children's physical health by affecting children's sports participation and screen time. To promote children's physical health, we should pay attention to the intervention of family sports attitude. 4) The mediating effects of exercise participation and screen time are similar in different family structures, so the structure of this study can be applied to different family structures.